2020
DOI: 10.1108/jhti-05-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of tourists’ emotional involvement on the relationship between destination attributes and tourist satisfaction

Abstract: PurposeThe study aims to examine the relationship between destination attributes and tourist satisfaction as well as the extent to which emotional involvement mediates between destination attributes and tourist satisfaction.Design/methodology/approachData were collected from a sample of 600 domestic tourists by using a purposive sampling technique where 382 samples were useable, and the response rate was 63.67%. The structural equation modeling (SmartPLS 3.0.) was used to test the hypothesized relationship amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 76 publications
6
48
0
4
Order By: Relevance
“…Customer satisfaction is considered to present a critical mean for measuring destination/hotel performance, as a satisfied customer is more likely to return and recommend destination/hotel (Biswas et al , 2020; Li et al , 2020). Existing literature has demonstrated that satisfaction should be a multi-item measure (Correia et al , 2013; Stumpf et al , 2020), because tourists evaluate various factors related to satisfaction, including accommodation quality, catering services, transport accessibility and the uniqueness of a destination.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Customer satisfaction is considered to present a critical mean for measuring destination/hotel performance, as a satisfied customer is more likely to return and recommend destination/hotel (Biswas et al , 2020; Li et al , 2020). Existing literature has demonstrated that satisfaction should be a multi-item measure (Correia et al , 2013; Stumpf et al , 2020), because tourists evaluate various factors related to satisfaction, including accommodation quality, catering services, transport accessibility and the uniqueness of a destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, green attributes may satisfy consumer emotional needs (Su et al , 2020a; Tsai, 2020) by satisfying their altruistic preferences and activating their positive disposition, which ultimately enhances their satisfaction (Jeong et al , 2014). Consequently, Biswas et al (2020) contend that destination attributes should be addressed in a way that can increase tourist’s emotional involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To get a better knowledge about the tourist evaluation towards cultural/heritage attributes and tourist satisfaction on these attributes has a pivotal role for destination managers, planners, and marketers in terms of destination positioning and promoting (Chi & Qu, 2008;Yoon & Uysal, 2005). Many scholars have demonstrated that the general attributes of a destination impact and determine overall tourist satisfaction (Alegre & Garau, 2010;Biswas et al, 2020;Eusébio & Vieira, 2013;Johann & Ghose, 2018;Kozak, 2002). In addition, Ghosh and Sofique (2012) emphasise that heritage attractions have a key role in creating tourist satisfaction.…”
Section: Relationships Between Variables and Hypothesismentioning
confidence: 99%
“…The literature highlights several studies on the effect that the facilities and features of a tourist destination have on visitor satisfaction and loyalty (Baloglu et al, 2004;Eusébio & Vieira, 2013;Ozturk & Gogtas, 2016). Moreover, the impact of destination attributes on tourist satisfaction was examined by some prior studies (Albayrak & Caber, 2013;Alegre & Garau, 2010;Biswas et al, 2020;Hui et al, 2007;Kozak, 2002;Kwanisai & Vengesayi, 2016) or tourist loyalty (Vareiro et al, 2019). Moreover, these studies generally investigate the general features of a destination rather than on specific aspects such as culture or heritage.…”
Section: Introductionmentioning
confidence: 99%
“…Tourists make a subjective judgment on their satisfaction based on the attribute of a tourist destination performance and information on a tourist destination (Sohn et al, 2016). The attribute of a positive tourist destination image generates satisfaction (Biswas et al, 2020). Therefore, the positive and negative attribute is important for assessing the experience of tourist's visits (Yoon & Uysal, 2005).…”
Section: Tourist Satisfactionmentioning
confidence: 99%